1989
DOI: 10.1677/jme.0.0030093
|View full text |Cite
|
Sign up to set email alerts
|

The androgen-dependent rat prostatic binding protein: comparison of the sequences in the 5′ part and upstream region of the Cl and C2 genes and analysis of their transcripts

Abstract: The complete gene encoding the polypeptide Cl of the complex androgen-controlled prostatic binding protein was isolated from a rat genomic library. A new genomic fragment (C2B) containing only the 5\ m=' \ part of a C2-related gene was also purified. The segments containing exon 1 and a large part of the adjacent sequences were analysed and compared with the corresponding region of the C2A gene which has been completely sequenced previously. The high structural similarity extending over a large part of all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Genes that are up-regulated by androgen in the prostate include prostate-specific antigen (PSA) (15,16), prostatein C3 (17), sex-limited protein (slp) (18), spermine-binding protein (19,20), prostate-binding protein C2A (21), cystatin-related protein 2 (22,23), calreticulin (24), and probasin (25,26). Androgen ablation-induced genes include clusterin͞sulfate glycoprotein-2 (SGP-2)͞testosterone repressed prostate mRNA-2 (TRPM-2) (27,28), transforming growth factor ␤ (29), rat ventral prostate gene 1 (RVP.1) (30), glutathione S-transferase (31), c-myc (32), c-fos (33), and matrix carboxyglutamic acid protein (30).…”
mentioning
confidence: 99%
“…Genes that are up-regulated by androgen in the prostate include prostate-specific antigen (PSA) (15,16), prostatein C3 (17), sex-limited protein (slp) (18), spermine-binding protein (19,20), prostate-binding protein C2A (21), cystatin-related protein 2 (22,23), calreticulin (24), and probasin (25,26). Androgen ablation-induced genes include clusterin͞sulfate glycoprotein-2 (SGP-2)͞testosterone repressed prostate mRNA-2 (TRPM-2) (27,28), transforming growth factor ␤ (29), rat ventral prostate gene 1 (RVP.1) (30), glutathione S-transferase (31), c-myc (32), c-fos (33), and matrix carboxyglutamic acid protein (30).…”
mentioning
confidence: 99%
“…It might be suggested that this non-palindromic sequence, either as repeat, or together with flanking sequences, might also have some function in steroid hormone responsive promoters in general. In this respect, it is of interest that TGTYCT sequences are present in the promoter of the androgen-dependent prostatic binding protein genes Cl, C2 and C3 (Claessens et al, 1989a). Furthermore, fragments from the promoter and first intron of the C3 gene that contain this consensus sequence have been shown to bind ARsteroid complex (Rushmere et al, 1987).…”
Section: Structural Features Of the Rat Ar Gene Promotermentioning
confidence: 99%
“…As a result, the activity of several promoters can be regulated by more than one of these receptors. Examples are the MMTV promoter, and the promoters of the C3, the cystatin-related protein (CRP) and the prostate specific antigen (PSA) gene (Ham et al 1988, Claessens et al 1989, De Vos et al 1994, Cleutjens et al 1997, Devos et al 1997. The consensus high affinity binding site of ER and ER is slightly different, 5 -AGGTCAnnnTGACCT-3 ( KleinHitpass et al 1989), therefore ER and ER direct the expression of a different panel of target genes.…”
Section: Introductionmentioning
confidence: 99%